Pengaruh Model Discovery Learning Berbantuan Media PhET Terhadap Kemampuan Berpikir Kritis Kelas X SMA - Mustika, Tina; Zulaiha, Fanni; Rifqi, Muhammad (Jurnal Pendidikan dan Ilmu Fisika, 2024)
This study aims to determine the effect of the discovery learning model assisted by PhET media on Alternative Energy material on the critical thinking skills of class X high school students in Cirebon city of 2024/2025 year. This type of research is a kuasi experiment. The research sample was an experimental class of 34 students and control class of 32 students with purposive sampling technique. The instrument was a student critical thinking skills test with the form of essay questions and has been validated by experts. In addition, based on the results of statistical tests, the instrument was declared valid and reliable with a value of 0.676. The average posttest score of the experimental class was 87 and the control class posttest was 81. The prerequisite test results stated that the samples were normally distributed and homogeneous. In addition, an independent t-test was conducted with a result of 0.002. These results indicate that there is a significant effect of the discovery learning model assisted by PhET media on Alternative Energy material for X grade high school students.